Optimizing Pipeline Inspection Program To Balance Safety, Compliance, And Cost Efficiency: A Case Study At Petrotama - Primasatria Zhes Putra; Akbar Adhi Utama (Eduvest - Journal of Universal Studies, 2025)
PetroTama operates an extensive pipelines network to support the production of 160,000 barrels of oil per day, equivalent to 26% of Indonesia’s daily production. These pipelines are used as a main oil transportation system in PetroTama, making it one of the main critical assets to sustain production performance. In order to maintain the production capacity, PetroTama has to ensure that the entire pipelines network operates safely and reliably that can only be achieved by implement robust pipeline inspection program. However, currently PetroTama is facing a significant gap with only 37% of its pipeline network inspected to date and leaving 5,480 km of pipelines having no inspection data. This condition also exposes PetroTama to serious impacts related to safety, compliance, and cost efficiency. The objective of this study is to evaluate the current conditions, identify root causes, and propose potential business solution for optimizing PetroTama’s pipeline inspection program by following DMAIC (Define, Measure, Analyze, Improve, Control) methodology. The main causes of the problems are assessed by utilizing Current Reality Tree (CRT) that reveals two primary root causes: budgetary constraints and the absence of regular improvement on the inspection program. The solution for this study is focused on the improvement of inspection program, since the budget availability is considered as a given condition. The Analytical Hierarchy Process (AHP) combined with Spreadsheet Simulation are used to find the best potential business solutions for the problems.